HUBUNGAN KUALITAS REVIU LAPORAN KEUANGAN DENGAN TEMUAN PEMERIKSAAN BPK PADA PEMERINTAH KABUPATEN/KOTA SE-DIY - Dwi Windarsih (Master in Accounting Program, 2014)
This study was conducted based on the phenomenon of audit results by State Audit Agency (BPK) of Republic Indonesia on local government’s financial statement which stating findings from examination towards the district / city governments in DIY, whether those already getting unqualified opinion or those categorized into qualified opinion. This is related to the obligation for Internal Supervisory Apparatus to conduct reviews on the financial statements of local governments (LKPD) before the statements audited by the BPK. This study uses mixed method i.e. it sequentially combines qualitative and quantitative methods of sequentially. The results suggested that the review quality conducted by each Inspectorate District / City is summarized as follows: Sleman District (82,56%), Yogyakarta city (81,28%), Kulon Progo District (80,00%), Bantul District (76,15%), and Gunungkidul District (73,08%). This review quality has a negative correlation with the amount of examination findings by BPK, which means that the better of the Review quality, the smaller the number of BPK findings. This is indicated by the value of correlative coefficient of -0.900. The results of this study are expected to provide information / feedback towards the policy makers to take the necessary measures, so that the Review implemented towards the financial statements by local authorities can be more qualified, thus minimizing the amount of examination conducted by BPK.